2006
DOI: 10.1242/jeb.02046
|View full text |Cite
|
Sign up to set email alerts
|

Cutting corners: the dynamics of turning behaviors in two primate species

Abstract: SUMMARY In an attempt to characterize more fully the variation in substrate reaction forces in the locomotor repertoire of primates, we recorded the forces involved in directional changes for two species. These are the first records of turning forces for vertebrate quadrupeds, much less primates. Three ring-tailed lemurs and two patas monkeys performed turns of approximately 30° as they crossed a force platform. The ring-tailed lemurs also turned on a horizontal branch-like support with a segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
35
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 28 publications
5
35
0
Order By: Relevance
“…The pattern in mice was attributed to a division of labor where front legs are primarily responsible for rotation and hindlegs responsible for deflection, which also takes advantage of the lower rotational inertia of the body at forelimbto-hindlimb step transitions. Similar differences among limb girdles are observed in some primate species (Demes et al, 2006). Other such divisions of labor, such as preferentially using one leg to turn, are also possible.…”
Section: Introductionsupporting
confidence: 56%
“…The pattern in mice was attributed to a division of labor where front legs are primarily responsible for rotation and hindlegs responsible for deflection, which also takes advantage of the lower rotational inertia of the body at forelimbto-hindlimb step transitions. Similar differences among limb girdles are observed in some primate species (Demes et al, 2006). Other such divisions of labor, such as preferentially using one leg to turn, are also possible.…”
Section: Introductionsupporting
confidence: 56%
“…Embracing behavioral variability within locomotor repertoires of free-ranging animals is an emerging topic among those who model the mechanics of animal performance (Dickinson et al, 2000;Alexander, 2002;Demes et al, 2006;Jindrich et al, 2007). One fundamental aspect of this variability is the ability of an organism to change its direction of travel, or maneuver through an obstacle-filled environment.…”
Section: Introductionmentioning
confidence: 99%
“…Quadrupedal animals that inhabit spatially complex arboreal habitats or mountainous areas, particularly those characterized by rugged vertical relief, may benefit from adaptations facilitating the capacity to change travel direction. Despite the seemingly integral importance of turning to locomotor performance, and despite the development of a descriptive protocol for categorizing turning behavior (Eilam, 1994;Walter, 2003;Demes et al, 2006;Jindrich et al, 2006;Jindrich et al, 2007), turning as a locomotor mode is rarely integrated into consensus frameworks for recording locomotor behavior in free-ranging animals (e.g. Prost, 1965;Hunt et al, 1996;Thorpe and Crompton, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Huey and Hertz, 1982;Huey and Hertz, 1984;Vilensky et al, 1994;Farley, 1997;Irschick and Jayne, 1998;Vanhooydonck and Van Damme, 2001), substrate width (e.g. Losos and Sinervo, 1989;Sinervo and Losos, 1991;Losos et al, 1993;Losos and Irschick, 1996;Bonser, 1999;Dunbar and Badam, 2000;Schmitt, 2003;Stevens, 2003;Lammers and Biknevicius, 2004;Demes et al, 2006) and texture (e.g. Zani, 2000;Claussen et al, 2002;Dai et al, 2002;Kerdok et al, 2002;Vanhooydonck et al, 2005) have all been shown to affect locomotor performance traits in a wide range of organisms.…”
mentioning
confidence: 99%